Uniqueness Problems about Entire Functions with Their Difference Operator Sharing Sets - Fan Niu; Jianming Qi; Zhiyong Zhou (Journal of Mathematics)
In this paper, we study the uniqueness questions of finite order transcendental entire functions and their difference operators sharing a set consisting of two distinct entire functions of finite smaller order. Our results in this paper improve the corresponding results from Liu (2009) and Li (2012).